ANALISIS KETERAMPILAN MENULIS TEKS IKLAN MENGGUNAKAN METODE PCP (POINT COUNTER POINT) SISWA KELAS V MI MIFTAHUL ULUM - Lailatusy Syifa’in Nadhiroh; Nanang Khoirul Umam (Institut Pendidikan Indonesia Garut, 2022)
This study examines writing and discussion techniques for fifth grade subjects in MI Miftahul Ulum. The aim is to present the method of learning subjects in the classroom. The research method used is descriptive qualitative with data analysis, data collection is done by means of observation, interviews, and documentation. “Data analysis is centered on understanding how students use knowledge and writing in their ad texts. By using the Point Counter Point method, students can better understand the information they are learning. This leads to increased participation and more dialogue among students. The results of this study revealed that the use of the PCP method improved memory, motor and perceptual development in students. Moreover, it is shown to be helpful in improving communication, reasoning, and perception among students. The PCP method uses four aspects of writing, each with an indicator consisting of multiple averages. These aspects include motor skills by 86.2%, behavioral traits by 93.1%, perception by 88.5%, and memory by 86.3%. When calculating the overall score for this indicator, the PCP method is considered one of the most effective ways to learn